La pianificazione paesaggistica in Italia Stato dell'arte e innovazioni - Magnaghi, Alberto (Territori, 2016)
In recent years, the in-depth analysis of landscape issues, the approval of the first regional Landscape Plans, the reflection on the action carried out by the Superintendencies are introducing a change of perspective in the protective action, drawing attention both to the critical aspects connected to it and to the numerous innovations emerged. This book presents the results of a research dedicated to Landscape Planning in Italy, offering a detailed state of the art, as well as some insights on the most significant initiatives. Finally, the volume proposes a methodological approach for an operational model of Landscape Planning based on a patrimonial and structural consideration of the landscape.